Ñande Rekó / Nosso modo de ser: o jopara no Jornal Diario Popular - Santos, Luciano Marcos dos (2013)
Identified by mixing Spanish and Guarani, the language jopara is common in informal or family environments in Paraguay. This thesis aims to understand the use of this language in the Diario Popular, especially in terms of news, titled sucesos on conflicts of urban life, mostly involving police incidents. Besides the analysis of the copies of the Daily Popular January to May 2012, data were obtained from literature. In this context, we verified the presence of the plurality of meanings of words present in the writing of the material, where the updates jopara forms of social distinction and classification, relating to people and genders in social situations themselves from public life. Thus, understanding the language in an interdisciplinary way, not as a source, but as a social practice, symbolic and historic use this notebook paper is a form of communication and expression evident in the tensions inherent in the demarcation of the differences between social groups.